Quantifying the Relationship Between the Medial Quadriceps Tendon–Femoral Ligament and Patellar Borders: A Pediatric Cadaveric Study. Issue 9 (July 2022) - Baskar, Danika; Stavinoha, Tyler J.; Sanchez, Mark; Gupta, Anshal; Randhawa, Sahej D.; Rohde, Matthew S.; Vuong, Brian; Tompkins, Marc A.; Ganley, Theodore J.; Ellis, Henry B.; Wilson, Philip L.; Fabricant, Peter D.; et al.
Background: The medial patellofemoral complex (MPFC) is a structure composed of the medial quadriceps tendon–femoral ligament (MQTFL) superiorly and the medial patellofemoral ligament (MPFL) inferiorly. The pediatric MPFL anatomy has been well described, but the precise anatomy of the MQTFL has only recently been described and studied in skeletally immature patients. Purpose: To describe the anatomic relationship between the MQTFL and its insertion on the quadriceps tendon and patella in pediatric specimens. Study Design: Descriptive laboratory study. Methods: A total of 22 pediatric cadaveric knee specimens were dissected to analyze attachment of the MQTFL to the quadriceps tendon and patella. Dissection was facilitated using lateral parapatellar arthrotomy followed by eversion of the extensor mechanism to evaluate MQTFL fibers from its undersurface. Results: The mean specimen age was 7.4 years. Specimens were divided based on age into a younger cohort (1-2 years), middle cohort (4-8 years), and older cohort (9-12 years). The quadriceps tendon attachment (QTA) of the MQTFL proximal to the patella extended a median of 5.0 mm in the younger cohort, 11.4 mm in the middle cohort, and 12.0 mm in the older cohort, with significant differences found between the younger and middle cohorts ( P < .047) and the younger and older cohorts ( P < .001). The QTA as a percentage of patellar articular height averaged 44.4% across all specimens. The vertical height of the patella measured a median of 14.0 mm, 22.3 mm, and 27.3 mm in the younger, middle, and older cohorts, respectively. Conclusion: This study expands on the recently described anatomy of the pediatric MPFC to quantify the anatomic relationship between the MQTFL attachment to the quadriceps tendon and patella in a more clinically relevant cohort of donor specimens. Clinical Relevance: As access to pediatric cadaveric tissue is extremely limited, a better understanding of MPFC and MQTFL anatomy will support surgeons in preoperative planning and intraoperative considerations for their approach to MQTFL and MPFL reconstruction. This may facilitate improved anatomic surgical stabilization of the patellofemoral joint in pediatric patients.